Microstructure-Based Constitutive Modelling of Low-Alloy Multiphase Trip Steels - Monsalve-Gonzalez, A; Carvajal-Ortega, L; Artigas-Abuin, A (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
The microstructure of low-alloy multiphase transformation-induced plasticity (TRIP) steels consists of ferrite, bainite, and metastable retained austenite, which can be transformed into martensite by plastic deformation. In some cases, residual martensite can be present in the initial microstructure. The mechanical behavior of these steels depends on the interaction between the intrinsic characteristics of the existing phases and the austenite stability. Due to these factors, the definition of their true stress-strain flow law is complex. This work presents the mechanical characterization of a phenomenological constitutive stress-strain flow law based on the Bouquerel et al. model, as evaluated for three TRIP steels of the same composition but undergoing different heat treatments. Morphological aspects of the existing phases, austenite stability, and suitable mixture laws between phases are considered. The model is found to accurately reproduce a true stress-strain flow law obtained under tensile uniaxial conditions and provide detailed information on the effective stress strain partition between the existing phases. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.